The development and initial findings of a DISGUST scale - Tobias Herzl; Jürgen Fuchshuber; Jürgen Fuchshuber; Jürgen Fuchshuber; Sarah Straßnig; Afrodita Latifi; Peter Walla; Peter Walla; Peter Walla; Andreas Fink; Human-Friedrich Unterrainer; Human-Friedrich Unterrainer; et al. (Frontiers in Human Neuroscience)
BackgroundDisgust is a fundamental emotion linked to survival, but its classification as a primary emotion remains debated. This study develops and validates a questionnaire assessing disgust as a primary emotion and examines its relationship with personality traits and psychopathology.MethodsA total of 482 German speaking participants completed an online survey. The sample was split for a principal component analysis (N = 250) and confirmatory (N = 232) factor analyses. Correlations and hierarchical regressions tested associations with personality traits and psychiatric symptoms.ResultsInitial item reduction via PCA resulted in two alternative unidimensional models with eight and five Items. CFA confirmed excellent model fit for both versions (DISGUST-8: χ2 = 13.00, p = 0.88, df = 20, χ2/df = 0.65, RMSEA = 0.000 (90% CI: 0.000, 0.057), CFI = 1.000; NFI = 0.992, TLI = 1.006, SRMR = 0.042; DISGUST-5: χ2 = 0.893, p = 0.97, df = 5, χ2/df = 0.18, RMSEA = 0.000 (90% CI: 0.000, 0.092); CFI = 1.000; NFI = 0.999; TLI = 1.011; SRMR = 0.017). Internal consistency was high for both versions (DISGUST-8: α = 0.89; DISGUST-5: α = 0.88). Trait disgust correlated highest with neuroticism (rDISGUST-8 = 0.36; rDISGUST-5 = 0.36) and anxiety (rDISGUST-8 = 0.27; rDISGUST-5 = 0.28). Regression analysis confirmed disgust as a significant predictor of neuroticism (t(457) = 4.19, β = 0.12).DiscussionThe findings highlight disgust’s role in personality and psychopathology. The developed scale reliably measures disgust, demonstrating its association with neuroticism. Future research should explore cross-cultural validation and refine the scale’s clinical applicability.